Sosialisasi Literasi Matematika PISA Berbasis Etnomatematika Pulau-Pulau Kecil Perbatasan pada Siswa Sekolah Menengah Pertama di Pulau Letti - Sigit Sugiarto; Michael Inuhan; Arche F. Bonara; Melati I. S. Umarella; John N. Lekitoo; Karolina Rupilele; Andy S. K. Dahoklory (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The mathematical literacy of Indonesian students based on the results of the PISA test held in 2022 was ranked 70th out of 81 countries participating in the test with a score of 366, which is far below the average score of 472. The results of the PISA test show the low mathematical literacy skills of students in Indonesia. This prompted the community service team to carry out socialization activities on PISA mathematical literacy based on ethnomathematics of small border islands on Letti Island. This socialization aims to introduce PISA mathematical literacy and provide practice and experience for students in working on mathematical literacy problems based on small border islands. This community service activity was carried out in Pulau Letti District on Wednesday, December 11, 2024. This socialization activity was attended by junior high school students in Pulau Letti District. The level of success in this socialization activity was measured using a questionnaire on the level of satisfaction and understanding of participants regarding the mathematical literacy material. The results of the questionnaire assessment showed that the socialization participants were very satisfied with the process of implementing the activity and were able to understand the socialization material very well. This activity is expected to be a sustainable.